2007
DOI: 10.1016/j.psychres.2006.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation, memory commission errors, and heightened autonomic reactivity

Abstract: If dissociative symptoms are manifestations of a psychological defense mechanism, one would expect people who have such symptoms to react with lower levels of physiological arousal and with memory omissions to emotionally provocative material. The current study tested this assumption in a sample of undergraduates. Sixty-two undergraduate students viewed a highly emotional video fragment. Pearson's product-moment correlations were calculated between dissociation (as indexed by the Dissociative Experiences Scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 53 publications
3
35
2
Order By: Relevance
“…This was not found to be the case in this study, which is in contrast with statements by some researchers suggesting that dissociation is related to memory distortion (e.g., Candel et al, 2003;Giesbrecht, Geraerts, & Merckelbach, 2007;Wright & LivingstonRaper, 2002) but is consistent with a more recent review (Dalenberg et al, 2012).…”
Section: Downloaded By [University Of Montana] At 16:35 09 April 2015contrasting
confidence: 72%
“…This was not found to be the case in this study, which is in contrast with statements by some researchers suggesting that dissociation is related to memory distortion (e.g., Candel et al, 2003;Giesbrecht, Geraerts, & Merckelbach, 2007;Wright & LivingstonRaper, 2002) but is consistent with a more recent review (Dalenberg et al, 2012).…”
Section: Downloaded By [University Of Montana] At 16:35 09 April 2015contrasting
confidence: 72%
“…In the study by Kollins et al [250], significant associations were identified between CPT commission errors and SNPs in the DRD2 gene (rs2075654, rs1079596), and between reaction time variability and a SNP in the NET gene (rs3785155). Errors of commission occurred when subjects answered a question incorrectly; a pattern of heightened emotional reactivity and commission errors is typical for individuals with elevated dissociation scores [251]. On the other hand, Hess et al [252] carried out association tests with DBH genotypes on four independent samples: healthy volunteers (n=387), patients presenting affective disorders (n=182), adult ADHD patients (n=407), and patients presenting personality disorders (n=637).…”
Section: Neurotransmittersmentioning
confidence: 99%
“…Previous studies detected in individuals with BPD an autonomic imbalance in provocation studies (Austin et al, 2007;Dixon-Gordon, Yiu, & Chapman, 2013;Giesbrecht, Geraerts, & Merckelbach, 2007). To our knowledge, few studies have assessed HRV in persons with DD, especially in stressful conditions (for a review, see van der Kruijs et al, 2012).…”
Section: Introductionmentioning
confidence: 99%